The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2009
DOI: 10.1109/aim.2009.5230010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a force sensor working with MR elastomers

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 23 publications
3
70
0
Order By: Relevance
“…A force sensor working with MR elastomer was designed by Li et al [73], shown in figure 29. The force sensor is designed to identify the normal loading.…”
Section: Sensing Devicesmentioning
confidence: 99%
“…A force sensor working with MR elastomer was designed by Li et al [73], shown in figure 29. The force sensor is designed to identify the normal loading.…”
Section: Sensing Devicesmentioning
confidence: 99%
“…In the approximation of the perfect elastic body, the sums of the main deformations and the compressibility module of MRE with graphite microparticles, depend on the magnetic field intensity. In our study [33], graphite was introduced into conventional MREs to change the overall resistances so that it can be detected by a multimeter. We found a MRE sample with 55% carbonyl iron, 20% silicon rubber and 25% graphite powder has the best performance.…”
Section: Mre Resistancesmentioning
confidence: 99%
“…They have found that the electrical resistance of the samples changes depended on both the magnitude of the mechanical loading and the strength of the magnetic field. In several other studies, it has been shown that a wider electrical resistance change of the composite can be obtained, and the sensitivity to the applied external force can be improved by the addition of graphite particles [21][22][23]. The change of the material conductivity for both the applied loading and the magnetic field could be explained by the change in the distance between particles.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to the field-dependent stiffness change property of the MRE, the electrical resistance of the material is also changed according to the induced strain within the elastomer [20][21][22][23]. Such a conductive property can be realized by the higher iron powder incorporation within the elastomeric matrix as well as the proper arrangement of the electrically conductive particles into the deforming direction of the host elastomer.…”
Section: Electrical Resistance Property Of a Graphite-based Elastomermentioning
confidence: 99%